1988
DOI: 10.1039/c39880000108
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity in complexes of ‘crowned’-phthalocyanines with metal salts

Abstract: ReferencesAggregation of 'crowned' phthalocyanines by metal salts increases the electrical conductivity compared to the non-aggregated phthalocyanines. In a previous paper we described the synthesis and aggregation behaviour of phthalocyanines which contain crown ether subunits, e.g. (I).4 Compound (1) forms aggreg ates in the presence of alkali metal ions5 (Figure 1). We now report that these aggregates exhibit increased electrical conductivity as compared to uncomplexed (1) and unsubsti tuted phthalocyanines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…The electrical properties of 2, its K , Rb and Cs picrate complexes and those of the polysiloxane derivatives have also been studied in the solid state by AC impedance spectroscopy [17,18,20]. Seebeck measurements showed that the uncomplexed CuPcs are p-type electronic conductors, whereas the metal picrate complexes of 2 exhibit ntype electronic conductivity.…”
Section: Electronic Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical properties of 2, its K , Rb and Cs picrate complexes and those of the polysiloxane derivatives have also been studied in the solid state by AC impedance spectroscopy [17,18,20]. Seebeck measurements showed that the uncomplexed CuPcs are p-type electronic conductors, whereas the metal picrate complexes of 2 exhibit ntype electronic conductivity.…”
Section: Electronic Conductivitymentioning
confidence: 99%
“…1). The complexes of 2 with K , Rb and Cs picrates were isolated and characterized [17,18], and in all cases the complexes were stacked in columns, with the cations located in (K ) or between (Rb and Cs ) the crown ether moieties.…”
Section: Introductionmentioning
confidence: 99%
“…1 [4], which are of particular interest in photoelectronic device development [9,10], 2) effective complexation to Li cations [11,12] and 3) significantly lowered isotropization temperature with respect to reference compounds with linear alkoxy chains [4]. Analogously, Pcʼs substituted with crown ethers have been studied extensively [13], specifically with regard to their complexation behavior and applicability for electronic and ionic conduction [14][15][16][17]. Each of these systems is particularly apt for the solubilization of inorganic salts, due to the complexation of cations by the ether moieties.…”
Section: Introductionmentioning
confidence: 99%
“…The crown-ether-fused phthalocyanine (Pc) molecules have also been reported as a supramolecular ion ± electron cooperative system. [15] The electrical conductivity of the Pc system was tuned through the cation-binding in the crown ether moieties. However, the electronic systems of these TCNQ and Pc compounds are essentially semiconducting or insulating.…”
Section: Introductionmentioning
confidence: 99%